2007
DOI: 10.3324/haematol.10910
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigens HLA DRB1 influence clinical outcome of chronic lymphocytic leukemia

Abstract: We investigated HLA DRB1 correlations with chronic lymphocytic leukemia (B-CLL) outcome in 90 patients. Neither of the alleles was associated with B-CLL clinical characteristics or mortality. HLA DRB1*01 and HLA DRB1*02-null were associated with shorter overall survival (p=0.007, p=0.002). Our results suggest that HLA-restricted adaptive immunity influences CLL outcome. Haematologica 2007; 92:5:710-711 B-cell chronic lymphocytic leukemia (B-CLL) is the most common adult leukemia in Western countries and Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Among Iranian patients, significant risk increase for disease progression was reported for HLA‐DRB1*04 and HLA‐DRB5 alleles, but they did not identify differences in HLA‐A or HLA‐B alleles or haplotypes . On the other hand, HLA‐DRB1*01 ( P ‐value = 0.007) and HLA‐DRB1*02‐null ( P ‐value = 0.002) were associated with shorter overall survival . One study of the nonclassical HLA loci suggested the presence of HLA‐E*01:03 allele and detection of soluble HLA‐E as an independent predictor of disease progression .…”
Section: Chronic Lymphocytic Leukaemia/small Lymphocytic Lymphomamentioning
confidence: 99%
“…Among Iranian patients, significant risk increase for disease progression was reported for HLA‐DRB1*04 and HLA‐DRB5 alleles, but they did not identify differences in HLA‐A or HLA‐B alleles or haplotypes . On the other hand, HLA‐DRB1*01 ( P ‐value = 0.007) and HLA‐DRB1*02‐null ( P ‐value = 0.002) were associated with shorter overall survival . One study of the nonclassical HLA loci suggested the presence of HLA‐E*01:03 allele and detection of soluble HLA‐E as an independent predictor of disease progression .…”
Section: Chronic Lymphocytic Leukaemia/small Lymphocytic Lymphomamentioning
confidence: 99%
“…Previous investigations examining the frequency of the HLA system in CLL patients demonstrated inconsistent and controversial association of some HLA alleles with CLL [17][18][19]22,23]. Whereas some studies indicated no association of CLL with HLA molecules [24], others demonstrated association with a variety of HLA alleles [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 97%
“…These polymorphic antigens could also influence the pathogenesis of B-cell or T-cell malignancies through continuous clonal stimulation of antigen-specific lymphocytes [16]. Many studies examined the possible association of the HLA system with lymphoproliferative disorders, but few reported HLA frequencies in CLL [17][18][19][20][21][22][23][24]. Furthermore, the frequency of HLA alleles has not been well determined in Asian CLL patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of the the HLA-DRB*02 and presence of the DRB*01 allele were related to adverse outcome of NHL and CLL, respectively [38,49]. In an extended haplotype analysis, HLA A*01 and B*08 components of 8.1 HLA ancestral haplotype exhibited the strongest associations with shorter FFP and OS in DLBCL patients [65,66].…”
Section: Role Of Hlamentioning
confidence: 95%